Towards Sustainable Transportation: Drivers Of Compressed Natural Gas Adoption in Dar Es Salaam City, Tanzania (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2025)
The adoption of compressed natural gas (CNG) vehicles has increased over the last decade, even in developing countries, in the pursuit of sustainable cities. This study examined the technological and environmental factors influencing CNG adoption as a vehicle fuel in Dar es Salaam, using a cross-sectional approach. It integrates quantitative survey data from vehicle owners with qualitative insights from interviews with natural gas sector stakeholders, transport operators, and policymakers. The analysis employs inferential statistics, including multiple response analysis, linear regression, and thematic analysis. Findings show a strong awareness of CNG’s environmental benefits, including a 73% reduction in greenhouse gas (GHG) emissions and a 67% decrease in pollution. However, concerns about the availability of CNG refueling stations (73%), compatibility with vehicles (67%), and maintenance services (58%) hinder adoption. Government policies play a crucial role in promoting CNG adoption, with subsidies and stricter emissions regulations serving as key motivators. Yet, public awareness campaigns are limited in effectiveness, revealing an insufficient understanding of CNG’s benefits. Overall, this study emphasizes the need for collaboration between government and private sector stakeholders to enhance CNG adoption in Dar es Salaam, advancing toward a sustainable transportation system that improves air quality and reduces greenhouse gas emissions.